EKSTRAKSI ASAM HUMAT PUPUK KANDANG SAPI DAN PENGARUHNYA UNTUK MENINGKATKAN EFEKTIVITAS PEMUPUKAN NITROGEN DARI BEBERAPA SUMBER PADA TANAMAN BAYAM - Mohamad Ihsan Tri Rahayu (AGRONOMIKA, 2018)
Research about extract of humic acid from cow manure for the efectiveness fertilization severel source of nitrogen fertilizer on spinach had conducted in Banyuanyar village district of Banjarsari Surakarta on July - September 2017.The factorial Completely Randomized Design method used with three replication. There were two treatments application that were source of nitrogen fertilizer (N) which three kind that were: urea (N1), KNO3 (N2), and NPK Mutiara compound fertilizer (N3). The second factor was application of humic acid  (H), with three levels that were: no humic acid (H0), 5 % of humic acid (N1), 10 % of humic acid (N2), and 15 % of humic acid (N3). From the research can be concluded that source of nitrogen fertilizer treatment and gave significant influence for the plant height, fresh weight of plant, dry weight of plant, and fresh weight of root. The dosage of humic acid application gave significant influence for all parameters observed. There were significant interaction between source of nitrogen fertilizer and dose of humic acid application on  parameters fresh weight of plant and fresh weight of root. Urea was the best fertilizer for spinach, and the best dosage of humic acid was 5 %.